Tinjauan Minat Beli Pelanggan Di Komuka Kafe Jakarta - Marini, Sri; Andriana Suhanda, Tina; Kenny Jonathan Adam, Reyhand; Rosdiana Aprilia, Lu'luwatin (JURNAL PARIWISATA VOKASI, 2024)
The study aims to determine the buying interest of Komuka cafe Jakarta customers. The problem in the study is how transactional interest, preferential interest, referential interest and exploratory interest of customers in buying products. The research method is descriptive method. The data collection technique was carried out by distributing questionnaires and observations. The data analysis technique uses a Likert scale. Based on the results of the study, it can be seen that customer buying interest at Komuka Kafe Jakarta is not yet in the good category. The suggestion given is the need to develop a variety of food and beverage products, so that the many choices provided can increase transactional interest. Developing innovations in terms of room decoration and building a better cafe atmosphere so that it can increase customer initiative to share positive comments and recommend the cafe to other customers. Providing discounts or special prices for loyal customers to enable customers to prioritize the locus as a place to visit. Expanding advertising and promotions to increase the explorative interest of its customers. In terms of social media, researchers suggest that more attention be paid to and updated with the latest information, so that it affects customer buying interest.